The Influence of Digital Marketing on Purchase Decision on Culture Products at Viera Oleh - Oleh in Pekanbaru City - Aulia, Viska; Berampu, Lailan Tawila; Wildah, Sri Wahyuni (CV. Rayyan Dwi Bharata, 2025)
this study aims to find out and analyze how the Influence of Digital Marketing on Purchase Decion on Culture Products in Viera Oleh-Oleh of Pekanbaru City. This study used 112 respondents as samples taken from the purposive sampling technique. The approach used in this study is quantitative by using the Partial Least Square model and SmartPls 4.0 software as tools for this research. The results of this study reveal that there is a significant influence of social media marketing on brand awareness on Ketan Talam Durian at Viera Oleh-Oleh, there is a significant influence of electronic word of mouth on brand awareness on Ketan Talam Durian at Viera Oleh-Oleh, there is a significant influence of brand awareness on purchase decision on Ketan Talam Durian at Viera Oleh-Oleh, there is a significant influence of digital marketing on purchase decision on Ketan Talam Durian at Viera Oleh-Oleh, there is a significant influence of digital marketing on purchase decision through brand awareness on Ketan Talam Durian at Viera Oleh-Oleh.